2016
DOI: 10.1038/mtna.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection Against Human Colorectal Cancer Xenografts Identifies an Aptamer That Targets RNA Helicase Protein DHX9

Abstract: The ability to selectively target disease-related tissues with molecules is critical to the design of effective therapeutic and diagnostic reagents. Recognizing the differences between the in vivo environment and in vitro conditions, we employed an in vivo selection strategy to identify RNA aptamers (targeting motifs) that could localize to tumor in situ. One of the selected molecules is an aptamer that binds to the protein DHX9, an RNA helicase that is known to be upregulated in colorectal cancer. Upon system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…[43]. DHX9 is closely related to the development of various cancers, such as breast cancer [44], colon cancer [45], lung cancer [40], liver cancer [46], Ewing sarcoma [47], and so on. DHX9 can bind to the inverted complementary ALU sequences which lie in the flank of circRNAs to reduce the formation of circRNAs [19].…”
Section: Discussionmentioning
confidence: 99%
“…[43]. DHX9 is closely related to the development of various cancers, such as breast cancer [44], colon cancer [45], lung cancer [40], liver cancer [46], Ewing sarcoma [47], and so on. DHX9 can bind to the inverted complementary ALU sequences which lie in the flank of circRNAs to reduce the formation of circRNAs [19].…”
Section: Discussionmentioning
confidence: 99%
“…DExH-Box Helicase 9 (DHX9) is a member of the DEAH-containing family of RNA helicases which has the ability to bind RNAs and catalyze the ATP-dependent unwinding of double-stranded RNAs (dsRNAs) [35]. It has been reported it is dysregulated in multiple human cancers [20], [21]. In this study, we found that the overexpression of SNORA42 suppressed the degradation of DHX9 and ubiquitination of DHX9, whereas had no effects on DHX9 mRNA level, indicating that SNORA42 promotes DHX9 expression by inhibiting its degradation, not the generation.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo SELEX is a direct and reliable technique for the identification of aptamers that selectively recognize diseased organs or tissues in animal models. 17 Using selected aptamers, we can develop targeting moiety-equipped nano-based delivery systems with high efficiency and specificity to overcome particularly robust biological barrier, such as bone and brain, and realize targeted drug delivery. The tumor endothelial cell-based active targeting strategy developed in this study can deliver therapeutics to tumor adjacent area to kill cancer cells and has great value in targeting tumor endothelial cells.…”
Section: Discussionmentioning
confidence: 99%